P-BN27 Novel technique for safe and efficient cannulation of the cystic and common bile duct. (16th December 2021) - Khan, Khurram; McLellan, Morag; Mahmud, Sajid
Abstract: Background: Concomitant stones in the common bile duct (CBD) at the time of laparoscopic cholecystectomy (LC) are present in up to 15% of patients.  In conjunction with intra-operative cholangiogram (IOC), transcystic common bile duct exploration (TCBDE) enables diagnosis and management of ductal stones in a single stage procedure.  However, cannulation of the cystic duct (CD) and CBD can be challenging.  With repeated attempts at cannulation, there is increased risk of iatrogenic injury by creating a false passage or perforating the duct.  We propose a novel technique for the safe cannulation of the CD and CBD. Methods: Once critical view of safety is achieved, a clip is placed distally in the CD and opened with scissors.  A flexible tip 80cm guidewire is then preloaded into 5-French ureteric catheter. The complex is then passed into the introducer through the lateral port. A grasper placed at Hartmann's pouch is used to retract the gallbladder and straighting the CD. Only the guidewire is advanced out of the catheter, traversing the CD and CBD. Once safely advanced, the catheter can then be slid over the guidewire and the guidewire can be removed. IOC and TCBDE can then be performed if indicated. Results: This technique was performed on 18 patients who failed CD cannulation during elective and emergency LC for symptomatic gallstone disease in a single center performed by the same surgical team.  Median age was 46 years and there was 15 females.  A total of 34 cannulations were attempted (in 18 patients) which 100% success rate.  There was no added time required for the technique.  In majority of cases it decreased the operative time due to quick intubation of CBD.  None of the cases required conversion to open surgery. Conclusions: The novel technique described for cannulation of the cystic duct uses a Seldinger 'like' approach. This is a safe an effective strategy for cannulation of the CD, making the skills more accessible and more time efficient. This should encourage more surgeons to perform IOC and TCBDE where indicated.